“English Learning Is Like…” : Metaphorical Perceptions of Prospective English Teachers About Language Learning Process - Heri Mudra; Nurul Aini (Universitas Islam Negeri (UIN) Syekh Wasil, Kediri, Indonesia, 2020)
The present study aimed to examine the attitudes and types of metaphorical perceptions of male and female prospective English teachers (PETs) towards their English learning process. Elicitation sheet with the prompt â€œEnglish learning is (like) â€¦ because â€¦â€ was used to collect the data. The data were qualitatively analyzed by listing, naming, categorizing, and determining the metaphors. The results of the elicited metaphors reveal that male and female PETsâ€™ attitudes towards English learning process include positive, negative, ambivalent, and neutral perceptions. Both male and female PETs viewed English learning in different attitudes. Male PETs generated more negative attitudes than the positive ones, while female PETs produced more positive attitudes than the negative ones. The findings also show that the metaphors were categorized into several types such as enjoyable activity, construction work, movement/journey, experience, planting/farming, exploration, and things. These types of metaphor imply the importance of the socio-cultural background of the learners. In conclusion, the metaphors help to determine appropriate strategies, methods, and materials for English teaching and learning.